Character Heroism in the Mecha Mobile Suit Gundam Anime Series: Iron-Blooded Orphans: A Psychoanalytic Study - Septiaji, Aji; Kusmana, Suherli; Syarifah, Eva Fitriani (Journal of Literature Language and Academic Studies, 2025)
Purpose- This study investigates the psychological dimensions of heroism in the anime Mobile Suit Gundam: Iron-Blooded Orphans (2015–2017), focusing on the characters Mikazuki Augus and Orga Itsuka. Set in a dystopian future where war and survival define the lives of young orphans, the anime provides a compelling narrative to examine how trauma, leadership, loyalty, and moral responsibility shape heroic behaviour. The background of this study lies in the underexplored intersection between anime, heroism, and psychoanalytic psychology. Methodology - This research employed a descriptive qualitative design. Data were collected through a literature study of all 50 episodes of the anime and supplemented with relevant scholarly sources. The analysis was grounded in Sigmund Freud’s psychoanalytic theory, particularly the concepts of the id, ego, and superego, to understand the psychological underpinnings of each character’s decisions and development. The data were processed through the stages of data reduction, data presentation, and conclusion. Findings - The study finds that heroism in Iron-Blooded Orphans is shaped by a complex interplay of internal conflicts, moral values, and social expectations. Mikazuki’s actions are driven by loyalty and emotional dependency on Orga, while Orga’s decisions reflect the burden of leadership and psychological strain. Both characters exhibit behaviors influenced by their trauma and suppressed desires, with the id, ego, and superego dynamics influencing their perception of duty and sacrifice. These findings suggest that heroic behaviour in the anime is deeply tied to unresolved psychological tension and external moral pressures. Novelty - This research offers a novel contribution by applying Freudian psychoanalysis to anime character analysis—a framework rarely used in this context. It provides a detailed mapping of the psychological structures driving heroic behaviour in anime, expanding the discourse on character psychology in popular media. Significance - The study is particularly relevant for scholars and students of media psychology, literary and cultural studies, and anime studies. It demonstrates how anime can serve as a valuable lens for analyzing complex psychological themes, making it a useful reference for future interdisciplinary research on heroism, trauma, and identity in visual narratives.